Geologists of Russian origin in Latin America - Platon Tchoumatchenco; Alberto C. Riccardi; Michel Durand Delga; Ricardo Alonso; Michel Wiasemsky; Demetrio Boltovskoy; Reynaldo Charrier; Elena Minina (Revista del Museo de La Plata)
We describe here the life and career of geologists   who beyond their nationality (Russian, Ukrainian, Tatar, German, etc.), were born on the territory of the Russian Empire, the Soviet Union or the Russian Federation  and  their descendants that  became geologists, all of whom  lived and worked in Latin-American  countries (where Spanish and Portuguese languages prevail).We include  also geologists from USSR who worked temporary in some countries of Latin America and left contributions to geology in form of publications.